Theory and praxis in the economic science - Σαραντίδης, Στυλιανός Α. (SPOUDAI Journal of Economics and Business, 2004)
This paper intends to cast some light on methodological issues of the economics science. First, a very short notice is made on latest developments in economics (Cleiometrics, evolutionary and experimental economics). Deductive and inductive methods on their historical framework are analyzed. Causality and randomness, indeterminateness are also phenomena teasing the economic theory. The meaning of "paradigm" of T. Kuhn is also introduced in our science. Empiricism and theoreticism stand viz a viz in this paper. Rational expectations and the bridging between theory and praxis, after a varificative procedure, are examined. Disagreements in the realm of economic policy, where conflicts are emerged, share a little space in the paper. A short reference is also made in Keynesian and meta-Keynesian economics. Lastly, some questions are put from theory of the firm and the macroeconomic forecasting. Is economic forecasting a scientific method, since economics is an empirical and social branch of human knowledge? JEL Classification: All, BOO